(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Antioxidants from natural sources are gaining demand in various industries since they are the safest alternatives to synthetic antioxidants. Marine macroalgae are rich sources of antioxidants and polyphenols. In the present study, in vitro antioxidant activities of the acetone extract, aqueous extract, and acetone: water extracts (7:3 v/v) of three macroalgae (Ulva fasciata, Gracilaria corticata, and Hypnea valentiae) collected from Thirumullavaram, Kerala, Southwestern coast of India were evaluated using three in vitro assays, viz., DPPH, ABTS+, NO* radical scavenging activities. The total phenolic content of the extracts was determined using the Folin-ciocalteau method and the results are expressed in milligrams of phloroglucinol equivalents per gram of dry weight (mg PGA g-1 DW). The highest DPPH radical scavenging was shown by acetone: water extract of U. fasciata (IC50 2.21 mg ml-1) and the highest ABTS+ radical scavenging was shown by the aqueous extract of G. corticata (IC50 0.13 mg ml-1) followed by the acetone extract of H. valentiae (IC50 0.14 mg ml-1). The highest NO* radical scavenging was exhibited by H. valentiae (IC50 0.06 mg ml-1). The acetone: water extracts of U. fasciata and G. corticata exhibited very high phenolic content (59.13 mg PGA g-1 DW and 59.85 mg PGA g-1 DW, respectively). The study indicated that all three species showed increasing radical scavenging activities corresponding to the concentration of the extract and the solvent used for extraction. The presence of secondary metabolites like phenols, and terpenes also seem to have contributed to the radical scavenging activities.